Sinifaná metasedimentites and relations with cajamarca paragneisses of the central cordillera of colombia (2012)
The western flank of Colombia’s Central Cordillera is characterized by N-S elongated tectonic blocks within the continental-scale Romeral and Cauca fault system. One of these blocks comprises the slates, metasandstones and quartzites of the Sinifaná Metasedimentites along with the intrusive Amagá granitic Stock. Zircon U-Pb detrital geochronology was conducted on a Sinifaná metaquartzite taken ca. 40 km southwest of Medellin. The main population yielded 640–500 Ma ages, typical of the Pan African-Brasiliano event and suggestive of Gondwanan provenance. The sample also yielded minor Proterozoic ages and the three youngest detrital zircons yielded 325–290 Ma ages. Taking into account the intrusive but unmetamorphosed character of the ca. 230 Ma Amagá Stock, we conclude that deposition of Sinifaná terrigenous rocks and their metamorphism occurred between the late Carboniferous and earliest Triassic.Sinifaná detrital-zircon populations are analogous to inherited zircon in Cajamarca migmatites and paragneisses from Las Palmas, near Medellin, which constitute the basement of the Tahamí terrane. This feature suggests a link between these high-grade metasedimentary rocks and the low grade metasedimentary rocks of the relatively small Sinifaná block. Metamorphic rims yielding 220–250 Ma, which are ubiquitous in Las Palmas, are absent in Sinifaná, probably due to very-low-grade metamorphism not producing zircon recrystallization. We propose that the tectonic block containing the Sinifaná metasedimentites may have broken away from a continental margin that once included both the Tahamí and other smaller pieces such as the Sinifaná. The age of tectonic departure is constrained by the block comprising the early Cretaceous Quebradagrande complex, which is currently positioned between the Tahamí and Sinifaná.